Procedures used for optically and infrared stimulated luminescence dating of sediments in Heidelberg - Lang, A.; Lindauer, S.; Kuhn, R.; Wagner, G. A. (Ancient TL, 1996)
This paper describes the procedures used for Optically Stimulated Luminescence (OSL) and Infrared Stimulated Luminescence (IRSL) in sediment dating at the Forschungsstelle Archäometrie in Heidelberg, Germany. The topics discussed include sampling, sample preparation, luminescence measurement, equivalent dose estimation and determination of dose rate.